The Sampeq of the Kenyah of East Kalimantan, Indonesia a case study of the recreational music tradition - Gorlinski, Virginia Kathleen (1989.)
The major goal in writing this thesis was to offer a detailed account of a non-gong tradition as a contribution toward balancing the ethnomusicological literature on Southeast Asia. The genre selected for intensive study was the sampeq (plucked lute) of the Kenyah people of East Kalimantan, Indonesia.
Thesis (M.A.)--University of Hawaii at Manoa.
Keywords: Music -- Indonesia -- East Kalimantan -- History and criticism